2001
DOI: 10.1164/ajrccm.163.6.2004150
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Expiratory Flow Limitation by Manual Compression of the Abdominal Wall

Abstract: We have assessed a new method, manual compression of the abdominal wall (MCA) during expiration, in the detection of expiratory flow limitation. Twelve stable patients with chronic obstructive pulmonary disease (COPD) and five normal subjects were studied during spontaneous breathing in the supine and seated posture. MCA was performed during expiration with one hand at the umbilical level and we measured flow, volume, pleural (Ppl) and gastric (Pga) pressures and abdominal anteroposterior (AP) diameter at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 16 publications
1
47
0
1
Order By: Relevance
“…Workers in Brussels, Belgium have shown that manual compression of the abdomen coinciding with the onset of expiration can be used as a simple way of detecting flow limitation at rest [57] and during exercise [58]. With one hand placed on the lower back of the patient and other applied with the palm at the level of the umbilicus perpendicular to the axis between the xiphoid process and the pubis, the operator first detects a respiratory rhythm by gentle palpation and then after warning the subject applies a forceful pressure at the onset of expiration.…”
Section: Squeezing the Abdomen During Expirationmentioning
confidence: 99%
“…Workers in Brussels, Belgium have shown that manual compression of the abdomen coinciding with the onset of expiration can be used as a simple way of detecting flow limitation at rest [57] and during exercise [58]. With one hand placed on the lower back of the patient and other applied with the palm at the level of the umbilicus perpendicular to the axis between the xiphoid process and the pubis, the operator first detects a respiratory rhythm by gentle palpation and then after warning the subject applies a forceful pressure at the onset of expiration.…”
Section: Squeezing the Abdomen During Expirationmentioning
confidence: 99%
“…The diagnosis of flow limitation with the manual compression of the abdominal maneuver is simple, does not require any device (apart from the availability of the flow-volume loop), and has been validated in spontaneously breathing subjects and in sedated mechanically ventilated subjects. [15][16][17] We measured auto-PEEP after a reasonably long endexpiratory pause (4 min) in order to reach an unambiguously stable value of auto-PEEP when trapped gas gradually decompresses into the central airways. 1 Therefore, auto-PEEP measurements should be reliable even in patients with severe inhomogeneous lung disease and long time constants.…”
Section: Discussionmentioning
confidence: 99%
“…14 After the occlusion maneuvers, the presence of flow limitation was assessed with manual compression of the abdomen. [15][16][17] Briefly, the investigator put one hand gently on the abdominal wall of the subject with the palm on the umbilicus oriented perpendicularly to the axis between the xiphoid process and the pubis. After a short period, which allowed for recognition of the expiratory phase, the investigator exerted firm but gentle compression of the abdomen in an antero-posterior direction as soon as the insufflation was finished.…”
Section: Protocolmentioning
confidence: 99%
“…The NEP (negative expiratory pressure) technique is widely used to diagnose EFL. It does however require a specific device, and in obese patients has some drawbacks [2,7,8]. PSCs do not require specific devices, but the patient must be very cooperative [4].…”
Section: Brief Commentmentioning
confidence: 99%